Ultrasound to Identify the Lumbar Space in Women With Impalpable Bony Landmarks Presenting for Elective Caesarean Delivery Under Spinal Anaesthesia: A Randomized Trial. Issue 3 (September 2017) - Creaney, M.; Mullane, D.; Casby, C.; Tan, T.
Abstract : ( Int J Obstet Anesth . 2016;28:12–16) The use of ultrasound-guided spinal anesthesia for cesarean delivery in patients with spinous processes that are difficult or impossible to palpate is gaining in popularity. The main aim of this study was to determine whether preprocedural ultrasound scanning would make it easier to locate an appropriate needle insertion point and thereby improve the performance of spinal anesthesia for elective cesarean delivery in patients with impalpable bony landmarks.